2017
DOI: 10.1039/c7lc00524e
|View full text |Cite
|
Sign up to set email alerts
|

An automated optofluidic biosensor platform combining interferometric sensors and injection moulded microfluidics

Abstract: A primary limitation preventing practical implementation of photonic biosensors within point-of-care platforms is their integration with fluidic automation subsystems. For most diagnostic applications, photonic biosensors require complex fluid handling protocols; this is especially prominent in the case of competitive immunoassays, commonly used for detection of low-concentration, low-molecular weight biomarkers. For this reason, complex automated microfluidic systems are needed to realise the full point-of-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Other research conducted by Szydzik et al aims to improve the functionality of injection molded microfluidics by introducing a novel method of integrating complex fluid handling into existing methods [32]. They argue that improved fluid handling in injection molded microfluidics will be required in order for this technique's full potential to be realized in point-of-care diagnostics.…”
Section: Injection Moldingmentioning
confidence: 99%
“…Other research conducted by Szydzik et al aims to improve the functionality of injection molded microfluidics by introducing a novel method of integrating complex fluid handling into existing methods [32]. They argue that improved fluid handling in injection molded microfluidics will be required in order for this technique's full potential to be realized in point-of-care diagnostics.…”
Section: Injection Moldingmentioning
confidence: 99%
“…In 2017, Szydzik et al reported a multiplexed BiMW‐based biosensor chip integrated with pneumatic valve‐based microfluidic modules offering a high degree of flexible, automatic and on‐chip sequential manipulation of multiple fluidic samples. [ 192 ] As illustrated in Figure a,b, utilizing a one‐step injection molding technique, a thin PDMS slab‐based microfluidic channel was integrated with the silicon sensor chip and also a thick PDMS interface slab. An automatic competitive immunoassay was performed with “cycles” of reference and competitive assays for detecting tetracycline antibiotics.…”
Section: Laboratory Prototypes Toward Poc Applicationsmentioning
confidence: 99%
“…On-chip microfluidic fluid handling technologies have been applied to highly complex applications, 7 including gene expression profiling, 208,209 polymerase chain reaction, 210 cell culture platforms 211,212 , single cell analysis, 184,213 and biosensor integration. 214,215 While complex microfluidic systems have been demonstrated with a high degree of sophistication within these areas of application, little evidence exists in the literature of development of these high throughput systems with a specific focus on manipulation of whole blood. While it is possible that this delayed application is due to fabrication impracticalities, 216 challenges associated with hemocompatibility could also play a role, and it is possible that achieving the full potential that complex on-chip microfluidic systems have demonstrated in other application areas may be dependent on careful consideration of material and operational hemocompatibility.…”
Section: Microfluidic Technologies For On-chip Blood Manipulationmentioning
confidence: 99%